Analysis of the Implementation of Electronic Medical Records Using the HOT-Fit Method with Data Integration as an Intervening Variable at Assyifa Women and Children Hospital, Tangerang City - Ryzha Ryskyanty; Munawar Munawar; Anastina Tahjoo (Lembaga Pengembangan Kinerja Dosen, 2025)
Human Organization Technology Net-Benefit (HOT-Fit) model is used to analyze information systems through 4 (four) dimensions: people, organization, technology, and net benefits. This study aims to analyze the implementation of RME with the HOT-Fit approach through data integration at RSIA Assyifa, Tangerang City. The research method is quantitative with data collection using a questionnaire distributed via Google Form. The sample consisted of 95 respondents of health workers and non-health workers who used RME. Data analysis was carried out using Structural Equation Modeling-Partial Least Square (SEM-PLS) version 3.0. In this study, there are 22 hypotheses, consisting of 17 direct influences and 5 (five) indirect influences. The results of the study show that system quality, information quality, and service quality have a significant positive effect on system use. Furthermore, system quality and information quality have a significant positive effect on user satisfaction, but service satisfaction does not affect user satisfaction. Next, system quality has a significant positive effect on organizational structure, as well as service quality which has a significant positive effect on the organizational environment. In addition, the organizational environment has a significant positive effect on net benefits, but in contrast to the variables of system usage, user satisfaction, and organizational structure which do not have a significant effect on net benefits. Related to the organizational aspect, the net benefit aspect, and data integration have a significant positive effect on RME implementation, while the technology aspect and human aspect do not have a significant effect on RME implementation. Data integration mediates the indirect effect of the technology aspect, the organization aspect, and the net benefit aspect on RME implementation, while data integration does not mediate the effect of the human aspect on RME implementation.